Effect of Activator on Levels of C, N, P and K Compost of Salak Sidimpuan Leaf Midrib - Rizky Amnah; Meiliana Friska (Jurnal Pertanian Tropik, 2019)
Salak Sidimpuan leaf midrib is abundant pruning waste. Salak Sidimpuan leaf midrib can becomposted containing a number of nutrients (carbon, Nitrogen, phosphorus, and potassium) for plantgrowth. To speed up the process of composting of salak leaf midrib can be done by giving a numberof activators. This study aims to see the effect of activator on the level of elements C, N, P and Kcompost of salak Sidimpuan leaf midribs. This study used a one-factor randomized block design with4 levels of treatment of activator, K0 = control, K1 = chopped midribs+cow manure fertilizer, K2 =chopped midribs+EM4, K3 = chopped midribs+cow manure fertilizer+EM4) with three replications.Data were analyzed with ANOVA and continued with DMRT test at 5% level if the F test showed areal effect. The results showed that the K2 with treatment chopped salak Sidimpuan leaf midrib andEM4 activator tended to give the best results in reducing the levels of C-organic and C/N ratio aswell as increasing total Nitrogen, total phosphorus and total potassium after composting comparedto other activator delivery treatments.